The Calculation of Time and Cost Estimation on Implementing Box Girder with Balance Cantilever Method in the Cakung Fly Over Project - Metar, Ryan Dordia Wiratama; Prajitno, Achmad Faiz Hadi; Zuhdy, Akhmad Yusuf (Jurnal Transportasi: Sistem, Material, dan Infrastruktur, 2023)
The Cakung Flyover Development Project is one of the programs of the DKI Jakarta Provincial government, through the Bina Marga of DKI Jakarta Province 2019-2020 which will build several non-level intersections in the form of underpasses and flyovers with the aim of reducing traffic jams in the capital region, more specifically congestion which often occurs in the East Primary Sentra area, namely on the Jatinegara-Bekasi railroad line. The Cakung Flyover is located in I Gusti Ngurah Rai Street and turns towards the new Cakung road by passing the Jakarta-Bekasi railroad crossing. This Flyover has a length of 760 meters and a width of 18 meters with the longest span of 80m from P8 and P9 which turn towards the new Cakung road and is between the railroad crossings. This Flyover used the Balance Cantilever Cast in situ method with the traveler form in Box Girder work from P7 to P10. This Applied Final Project discusses about the estimated time and cost needed to complete the Cakung Flyover structure starting from P7 to P10 on the 180meter box girder work consisting of 32 segments using the balance cantilever method with the traveler form. Based on the analysis carried out, the results were obtained